SISTEM INFORMASI PELAYANAN PUBLIK DESA SATU PINTU BERBASIS WEB - Mutiara, Linda; -, Yuliadi; Mulyanto, Yudi; -, Rodianto; Ikram, Fadhli Dzil; Ismiyarti, Wilia; Rosika, Herliana (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2024)
The Web-Based One-Stop Village Public Service Information System (Case Study: Senawang Village Office, Orong Telu District) was completed using Visual Studio Code, Codeigniter programming language, and MySQL database. The research method used is qualitative, and the software development method, Prototype method, and system design method use four Unified Modeling Language (UML) diagrams consisting of use case diagrams, activity diagrams, sequence diagrams, and class diagrams. It has passed the testing process using Black Box. It has successfully provided information to users (Community) regarding services, namely birth report data, death reports, registration of migrants, applications for moving residents, and applications for certificates of incapacity. It can make complaints on the website link of the Senawang Village Office, Orong Telu District, Sumbawa Regency, West Nusa Tenggara.